Combined Primary Cleft Lip and Palate Repair: Is It Safe?. Issue 2 (March 2019) - Kantar, Rami S.; Rifkin, William J.; Cammarata, Michael J.; Maliha, Samantha G.; Diaz-Siso, J. Rodrigo; Farber, Scott J.; Flores, Roberto L.
Abstract : Background: Single-stage primary cleft lip and palate (PCLP) repair is controversial in the United States, and most patients are treated with a staged approach. In this study, early postoperative complications of the single-stage approach as compared to primary cleft lip (PCL) or primary cleft palate (PCP) alone were evaluated. This study represents the largest cohort of patients undergoing combined cleft lip and palate repair. Methods: The American College of Surgeons National Surgical Quality Improvement Program-Pediatric database was used to identify patients undergoing single-stage PCLP, PCL, or PCP repairs. Preoperative factors and postoperative outcomes were compared between the 3 groups, as well as within the PCLP group between patients with and without complications. Univariate and multivariate analyses were performed. Results: A total of: 181 patients were included in the single-stage PCLP group, 1007 in the PCP group and 783 in the PCL group. There was no difference in the rates of early complications between the 3 groups. Within the PCLP group, cardiac risk factors (β = 35.19; 95% confidence interval [CI] 7.88–75.21; P  = 0.04) and complications (β = 77.31; 95% CI 35.82–118.79; P  < 0.001) were significant risk factors for longer operative time. Conclusion: Analysis of a national database showed that single-stage PCLP repair is not associated with increased risk of early postoperative complications as compared to primary lip or palate repair alone. In-depth long-term analyses of craniofacial morphology, fistulae rate, speech, and dental outcomes are essential for a comprehensive assessment of the effects of combined cleft lip and palate repair.